Evaluation of the UNDP Strategic Plan and Global and Regional Programmes - Programme des Nations Unies pour le Développement (United Nations, 2017)
IEO and UNDP carried out an ‘Evaluation of the UNDP Strategic Plan, Global Programme, and Regional Programmes (2014-17)’ with the purpose of strengthening UNDP accountability to global and national development partners, supporting the development of the next Strategic Plan, and supporting organizational learning. The evaluation was designed to inform both internal and external stakeholders of how UNDP is addressing development challenges. The evaluation assessed the outcomes of the Strategic Plan, and the implementation of global, regional and country-level programming, to ascertain whether UNDP is making progress in achieving its stated goals, and whether the Strategic Plan, Global Programme, and Regional Programmes are serving as effective tools for organizing and guiding UNDP programming and activities.